Improved Performance of Silicon Rubber Insulation with Coal Fly Ash Micro Filler - Tajuddin Waris; Yoshinobu Murakami; Naohiro Hozumi; Tomohiro Kawashima; Salama Manjang; Ikhlas Kitta (EPI International Journal of Engineering, 2018)
This paper presents the effect of coal fly Ash filler (CFA) on the electrical properties of silicon rubber composite. The observed electrical properties are volume resistance, surface resistance, and the surface breakdown voltage. The temperature The effect on the surface breakdown voltage of silicon rubber with CFA filler also was observed. The type of silicon used is RTV 683. The filler concentrations of the matrix are 0,​​10.20,30,40 per-hundred gram of resin (phr). The test results show that the surface resistance increased significantly with the increasing of CFA loading filler. The increasing of volume resistance is nonlinear; the volume resistance tends to decrease when the CFA loading filler exceeds 30 phr. Flashover test results show that flashover inception voltage (FOIV) increases with the increasing of CFA filler concentration and the increasing of temperature.